AI Methods in Algorithmic Composition: A Comprehensive Survey - Fernández-Rodríguez, Jose David; Vico-Vela, Francisco José (AI Access Foundation, 2013)
Algorithmic composition is the partial or total automation of the process of music composition by using computers. Since the 1950s, different computational techniques related to Artificial Intelligence have been used for algorithmic composition, including grammatical representations, probabilistic methods, neural networks, symbolic rule-based systems, constraint programming and evolutionary algorithms. This survey aims to be a comprehensive account of research on algorithmic composition, presenting a thorough view of the field for researchers in Artificial Intelligence.
Keywords: Inteligencia artificial; Algorithmic composition; Artificial intelligence; Computational creativity; Artificial creativity